Hubungan Antara Konsep Diri dengan Kualitas Hidup Pasien yang Menjalani Kemoterapi di Ruang Kemoterapi RS Urip Sumoharjo Tahun 2025 - Selvia Ajeng Pertiwi; Rika Damayanti; Ardinata Ardinata; Feri Agustriyani (Lembaga Pengembangan Kinerja Dosen, 2026)
The number of cancer cases worldwide based on GLOBOCAN 2020, an online database from the International Agency for Research on Cancer (IARC), reached 19.3 million cases in 2020, increasing compared to 18.1 million cases in 2018. This increase reflects the growing global burden of cancer and its impact on patients’ quality of life. This study aimed to determine the relationship between self-concept and quality of life among patients undergoing chemotherapy at RS Urip Sumoharjo in 2025. This study employed a quantitative research design with a cross-sectional approach. The research was conducted in November 2025 using an accidental sampling technique, involving a total of 58 respondents. Data were collected using questionnaires, and data analysis was performed using computer-based statistical analysis with the Gamma test. The results showed a significant relationship between self-concept and quality of life among patients undergoing chemotherapy, with a p-value of 0.000 (p < 0.05). In addition, the correlation coefficient (r) was 0.931, indicating a very strong and positive relationship. These findings suggest that patients with a more positive self-concept tend to have a better quality of life while undergoing chemotherapy. It is recommended that patients improve self-understanding and self-acceptance through active participation in educational and counseling programs provided by healthcare facilities, in order to enhance their quality of life during chemotherapy.